2011
DOI: 10.4103/0976-3147.80084
|View full text |Cite
|
Sign up to set email alerts
|

Retromastoid-sub occipital: A novel approach to cerebello pontine angle in acoustic neuroma surgery-our experience in 21 cases

Abstract: Background:Acoustic neuroma surgery poses significant challenges regarding definite management and preservation of hearing and the facial nerve are of great concern.Aim:To analyze the efficacy of the retromastoid approach in acoustic neuroma surgery.Materials and Methods:Tumors operated between January 2002 and December 2008, by the authors, using the retromastoid approach, were analyzed. Twenty-one patients who presented with acoustic tumor were considered for this study.Discussion:Precise knowledge of the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…House-Brackmann grade I-II) in more than 90 per cent of patients. 7 In our study, 19 tumours were completely excised, 5 of which were cystic. We found that cystic tumours were tightly adherent to the facial nerve or to other cranial nerves, making complete tumour excision more difficult and sometimes impossible without significant risk.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…House-Brackmann grade I-II) in more than 90 per cent of patients. 7 In our study, 19 tumours were completely excised, 5 of which were cystic. We found that cystic tumours were tightly adherent to the facial nerve or to other cranial nerves, making complete tumour excision more difficult and sometimes impossible without significant risk.…”
Section: Discussionmentioning
confidence: 99%
“…The inferior portions of the cerebellopontine angle and the posterior surface of the temporal bone anterior to the porus acousticus are clearly observed. 7 The disadvantages of the retromastoid approach are: (1) it may require cerebellar retraction; and (2) manipulation of the cerebellum provides opportunities for post-operative oedema, haematoma, infarction and haemorrhage. 7 Experience has a remarkable influence on the outcome of vestibular schwannoma surgery, as well as on the prevalence of surgical morbidity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations